Brain Computer Interface to operate domotic environment - Fabio Aloise; E. Morabito; A. Riccio; M. Risetti; D. Mattia; M. Mecella; Tiziana Catarci; F. Babiloni; S. Salinari; F. Cincotti (Interaction Design and Architecture(s), 2009)
The brain computer interface (BCI) technology allows a direct connection between brain and computer without any muscular activity required, and thus it offers a unique opportunity to enhance and/or to restore communication and actions into external word in people with severe motor disability. Here we present a set of findings that confirm the feasibility of a real domotic environmental control operated via P300-based BCI. Furthermore, the relevant issue of a low bit rate of command execution is addressed by the implementation of a dynamical BCI interface whose upgrade is based on a continuous real- time collection of information from the environment.